Electrodeposition and characterisation of CuInSe2 for applications in thin film solar cells - De Silva, K.T.L.; Jayanetti, J. K. D. S.; Chithrani, B.D.; Priyantha, W.A.A.; Siripala, W. (My University, 2001)
Copper indium diselenide ŽCuInSe2. layers have been grown at room temperature by electrochemical deposition technique in an aqueous medium. Resulting thin films have been characterised using XRD, XRF, XPS, GDOES and SEM for structural, stoichiometric and morphological properties. A considerable influence of the deposition potential on the atomic composition of In and Se present in the film was observed. Cu composition remains the same within the deposition potentials used in this investigation. The deposited layers are polycrystalline and annealing at 350 C for 30 min improves the crystallinity. The film quality deteriorates due to dissociation when annealed at temperatures above 350 C. Excessive annealing results in a surface which is depleted in Cu and rich in In and Se